Analisis Kebutuhan dalam Perancangan Sistem Inventory Hotel untuk Meningkatkan Efisiensi Pengelolaan Barang dan Stok - Dede Wira Trise Putra (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
The demand for information systems continues to rise in line with the advancement of technology and the changing times. Every industrial sector is now required to adapt, including the hospitality industry. One of the crucial aspects of hotel management is the transaction recording system, particularly related to the management of consumable inventory. To this day, many hotels still rely on conventional methods such as manual bookkeeping or simple spreadsheets. These traditional methods are prone to human error, time-consuming, and make real-time inventory checking and reporting difficult. Given these conditions, there is a need to develop an integrated and efficient inventory information system. This system is designed to facilitate the recording and monitoring of consumable stock availability, including inventory levels and transactions with suppliers. With such a system in place, hotel management can accurately monitor stock levels and plan procurement according to actual needs, avoiding shortages or overstocking. The development of this system follows the stages of the Software Development Life Cycle (SDLC), beginning with the requirement analysis phase. This phase involves gathering information from users, which is then visualized in the form of several design tools: the Use Case Diagram to illustrate the interactions between users and the system, the Entity Relationship Diagram (ERD) to design the database structure, and wireframes of the User Interface to ensure the system is easy to understand and use. The results of this design process indicate that the system being developed meets all user requirements in terms of both functionality and usability. With a well-structured and computerized inventory system, hotel inventory management can be carried out more effectively, efficiently, and with minimal error. Ultimately, this contributes to enhancing overall service quality and operational performance in the hospitality sector.